Improved strategies to counter the COVID-19 pandemic: Lockdowns vs. primary and community healthcare. (2021) - Farsalinos, Konstantinos; Poulas, Konstantinos; Kouretas, Dimitrios; Vantarakis, Apostolos; Leotsinidis, Michalis; Kouvelas, Dimitrios; Docea, Anca Oana; Kostoff, Ronald; Gerotziafas, Grigorios T.; Antoniou, Michael N.; Polosa, Riccardo; Barbouni, Anastastia; et al.
Graphical abstract: Highlights: The COVID-19 pandemic has challenged the healthcare capacity of many countries. Strict, horizontal lockdowns have adverse social, economic and health effects that have not been fully considered. Primary and community care have multiple roles in COVID-19 pandemic mitigation. Greece is a case example of a country which neglected primary and community care, and in November 2020 implemented a second horizontal lockdown. Primary and community care, represents the only realistic strategy for successful COVID-19 pandemic mitigation in the long-term. Abstract: COVID-19 pandemic mitigation strategies are mainly based on social distancing measures and healthcare system reinforcement. However, many countries in Europe and elsewhere implemented strict, horizontal lockdowns because of extensive viral spread in the community which challenges the capacity of the healthcare systems. However, strict lockdowns have various untintended adverse social, economic and health effects, which have yet to be fully elucidated, and have not been considered in models examining the effects of various mitigation measures. Unlike commonly suggested, the dilemma is not about health vs wealth because the economic devastation of long-lasting lockdowns will definitely have adverse health effects in the population. Furthermore, they cannot provide a lasting solution in pandemic containment, potentially resulting in a vicious cycle of consecutive lockdowns with in-between breaks. Hospital preparedness has been the main strategy used by governments. However, a major characteristic of the COVID-19 pandemic is the rapid viral transmission in populations with no immunity. Thus, even the best hospital system could not cope with the demand. Primary, community and home care are the only viable strategies that could achieve the goal of pandemic mitigation. We present the case example of Greece, a country which followed a strategy focused on hospital preparedness but failed to reinforce primary and community care. This, along with strategic mistakes in epidemiological surveillance, resulted in Greece implementing a second strict, horizontal lockdown and having one of the highest COVID-19 death rates in Europe during the second wave. We provide recommendations for measures that will reinstate primary and community care at the forefront in managing the current public health crisis by protecting hospitals from unnecessary admissions, providing primary and secondary prevention services in relation to COVID-19 and maintaining population health through treatment of non−COVID-19 conditions. This, together with more selective social distancing measures (instead of horizontal lockdowns), represents the only viable and realistic long-term strategy for COVID-19 pandemic mitigation.